THE PUBLIC RIGHT TO FLOAT THROUGH PRIVATE PROPERTY IN UTAH: CONATSER V. JOHNSON (Utah Environmental Law Review; Vol 29 No 1 (2009), 2009)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} In the summer of 2008, the Utah Supreme Court addressed the scope of the public’s easement in state waters. Specifically, the Court determined “whether the easement, which allows the public to engage in recreational activities in state waters, also allows the public the right to touch the privately owned beds below those waters.” The Supreme Court ruled that “[t]he district court [had] incorrectly interpreted the scope of the public’s easement in state waters so as to limit the Conatsers’ rights to being upon the water and to touching the privately owned bed of the Weber River only in ways incidental to the right of floatation.” In its decision, the Supreme Court found that under Utah law, the public has the right to “engage in all recreational activities that utilize the water” and that this right is not limited to “activities that can be performed upon the water.” While riparian land owners may see the Conatser ruling as a major step backwards in the protection of their property rights, recreation enthusiasts are likely to view the holding in this case as the right interpretation of the public’s easement over state waters in Utah. As the Court emphasized in its Conatser ruling, by statute all waters in Utah are property of the public. Under such a “doctrine of public ownership,” the public has an “easement over the waters regardless of who owns the water bed beneath.” The Conatser ruling resolved two issues: first, whether it is criminal trespass for members of the public to float on state waters through private property; and second, whether recreational users who float through private property on the state waters and touch the beds and banks of these streams are subject to being dragged into court by riparian land owners and charged with civil liability.